1996
DOI: 10.1108/02651339610127220
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the joint effect of brand and country image in consumer evaluation of global products

Abstract: States that few studies have attempted to measure the joint effect of brand and country images, or the dimensions of these images, on consumer evaluation of global products. Suggests a methodology for defining product value by consumers’ perception of brand and country image dimensions when sourced internationally. Brand‐country image profiles were factor analysed to provide dimensions of each brand‐country combination. Shows that consumer perception of product value changes, evidenced by brand‐country dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 24 publications
4
85
0
2
Order By: Relevance
“…Kaynak et al (2000) have shown that COO evaluations in a developing country differ from those in developed countries. Koreans have been found to be more prejudiced than Americans against less favourably evaluated countries (Nebenzahl and Jaffe, 1996). Jaffe and Martinez (1995) report that Mexicans are literally obsessed with USA and Japanese products.…”
Section: Country-of-origin Evaluationsmentioning
confidence: 99%
“…Kaynak et al (2000) have shown that COO evaluations in a developing country differ from those in developed countries. Koreans have been found to be more prejudiced than Americans against less favourably evaluated countries (Nebenzahl and Jaffe, 1996). Jaffe and Martinez (1995) report that Mexicans are literally obsessed with USA and Japanese products.…”
Section: Country-of-origin Evaluationsmentioning
confidence: 99%
“…Although access to low cost resources may enhance a firm's competitiveness in a global market place, country of origin (COO) has been shown to have an indirect influence on consumer purchasing behaviour (e.g., Berry, Mukherjee, Burton and Howlett 2015;Gurhan-Canli and Maheswarn 2000;Koschate-Fischer, Diamantopoulos and Oldenkotte 2012;Samiee 1994). The COO effect can be differentiated between brand origin and country of production (COP) considering the fact that a poorly perceived country of manufacturing may devalue the brand (e.g., Godey, Pederzoli, Aiello, Donvito, Chan, Oh, Singh, Skorobogatykh, Tsuchiya and Weitz, 2012;Haubl and Elrod 1999;Nebenzahl and Jaffe 1996). For example, a 'Made in China' label has been a subject of debate in terms of perceived product quality and its influence on consumer purchase decision.…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests that COO is a latent factor that assists product evaluation made by consumers (Ahmed and d'Astous, 2004;Kaynak et al, 2000;Nebenzahl and Jaffe, 1996;Srikatanyoo and Gnoth, 2002). Pappu et al (2006) said that brand equity changes as per the change in COO of the product, further argues that marketing managers who operates in the international arena must comprehend the importance of incorporating COO for brand equity measurement.…”
Section: Country Of Originmentioning
confidence: 99%